Molecular Features of Polycystic Ovary Syndrome Revealed by Transcriptome Analysis of Oocytes and Cumulus Cells - Li, Jie; Chen, Haixia; Gou, Mo; Tian, Chenglei; Wang, Huasong; Song, Xueru; Keefe, David L.; Bai, Xiaohong; Liu, Lin (Frontiers in Cell and Developmental Biology, 2021)
Polycystic ovary syndrome (PCOS) is typically characterized by polycystic ovarian morphology, hyperandrogenism, ovulatory dysfunction and infertility. Furthermore, PCOS patients undergoing ovarian stimulation have more oocytes, however, poor quality of oocytes leads to lower fertilization and implantation rates, decreased pregnancy and increased miscarriage rates. However, the complex molecular mechanisms underlying PCOS and poor quality of oocytes remain to be elucidated. We obtained matched oocytes and cumulus cells (CCs) from PCOS patients and compared them with age-matched, Controls, and performed RNA sequencing analysis to explore the transcriptional characteristics of their oocytes and CCs. Moreover, we validated our newly confirmed candidate genes for PCOS by immunofluorescence. Unsupervised clustering analysis showed overall global gene expression patterns and transposable elements (TEs) expression profiles of PCOS patients tightly clustered together, clearly distinct from those of controls. Abnormalities in functionally important pathways are found in PCOS oocytes. Notably, genes involved in microtubule processes, TUBB8 and TUBA1C, are overexpressed in PCOS oocytes. Also, metabolic and oxidative phosphorylation pathways are dysregulated in both oocytes and CCs from PCOS patients. Moreover, in oocytes differentially expressed TEs are not uniformly dispersed in the human chromosomes. Rather, endogenous retrovirus 1 (ERV1) elements located on chromosome 2,3,4,5 are highly upregulated. Interestingly, these correlate with the most highly expressed protein-coding genes, including tubulin-associated genes TUBA1C, TUBB8P8 and TUBB8, linking ERV1 elements to the occurrence of PCOS. Our comprehensive analysis of gene expression in oocytes and CCs, including global and TE expression, revealed specific molecular features of PCOS. Aberrantly elevated expression of TUBB8 and TUBA1C and ERV1 provides additional markers for PCOS and may contribute to the compromised oocyte developmental competence in PCOS patients. Our findings also may have implications for treatment strategies to improve oocyte maturation and pregnancy outcomes for women with PCOS.